2021
DOI: 10.3961/jpmph.21.139
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Compliance With Non-pharmaceutical Interventions and Social-distancing Policies in Korea During the COVID-19 Pandemic

Abstract: This study explored changes in individuals' behavior in response to social distancing (SD) levels and the "no gatherings of more than 5 people" (NGM5) rule in Korea during the coronavirus disease 2019 (COVID-19) pandemic.Methods: Using survey data from the COVID-19 Behavior Tracker, exploratory factor analysis extracted 3 preventive factors: maintenance of personal hygiene, avoiding going out, and avoiding meeting people. Each factor was used as a dependent variable. The chisquare test was used to compare diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Maintenance of personal hygiene, reduced time away from home, and avoidance of large gatherings strengthens physical distancing. 33 As the epidemic became severe, the physical distancing level increased, and subway use in Seoul decreased. 34 In addition, the transmission of COVID-19 infection was prevented by mandatory face masks in public facilities, along with prevention and control measures.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of personal hygiene, reduced time away from home, and avoidance of large gatherings strengthens physical distancing. 33 As the epidemic became severe, the physical distancing level increased, and subway use in Seoul decreased. 34 In addition, the transmission of COVID-19 infection was prevented by mandatory face masks in public facilities, along with prevention and control measures.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain why findings are equivocal and why some studies investigating age and gender produced null findings, but it may be because the relationship varies by the type of behaviour or it may be due to sampling bias or how the behaviour is defined and measured. Studies conducted in other countries have found a positive association between female gender and older age and adherence to TRBs during the Covid-19 pandemic [32][33][34][35][36][37][38][39] and previous pandemics [40]. These sociodemographic differences in behaviour may be explained by gender-and age-related differences in the psychological predictors of behaviour during the Covid-19 pandemic.…”
Section: Key Findingsmentioning
confidence: 91%
“…However, studies have discussed the “luxury nature” [ 2 ] of social distancing (i.e., unequal impact on human mobility according to socioeconomic status) during the COVID-19 pandemic [ 3 – 5 ]. In the Republic of Korea, social distancing policies strongly relied on the voluntary participation of citizens without mandates [ 6 ] and exhibited short-term changes. In this situation, the effects of such policies varied depending on each community’s capacity to comply.…”
Section: Introductionmentioning
confidence: 99%